An Intramolecular Diels–Alder Furan (IMDAF) Approach towards the Synthesis of Isoindolo[2,1-a]quinazolines and Isoindolo[1,2-b]quinazolines - Zaytsev, Vladimir P.; Revutskaya, Ekaterina L.; Nikanorova, Tatiana V.; Nikitina, Eugeniya V.; Dorovatovskii, Pavel V.; Khrustalev, Victor N.; Yagafarov, Niyaz Z.; Zubkov, Fedor I.; Varlamov, Alexey V. (Synthesis, 2017)
An efficient approach to bridged pentacyclic nitrogen heterocycles via the tandem acylation/intramolecular Diels–Alder furan (IMDAF) reaction of 2-furylquinazolinones is described. Reactions of α,β-unsaturated acid anhydrides with 2-furyl-2,3-dihydroquinazolin-4-ones give 6b,9-epoxyisoindolo[2,1-a]quinazolines in average yields. In this case, the exo-IMDAF reactions proceed with excellent diastereoselectivity giving five stereogenic centers and three new rings in one synthetic step. Isomeric 2,4a-epoxyisoindolo[1,2-b]quinazolines are obtained by one-pot, three-component condensation reactions of allylamine, isatoic anhydride and furaldehydes involving the same IMDAF reaction as the key step. Some useful transformations including halogenation, hydrogenation, Prilezhaev epoxidation, and esterification of the synthesized epoxyisoindoloquinazolines are also demonstrated.
Keywords: furans; Diels–Alder reaction; multicomponent reaction; isoindolo[2,1-a]quinazoline; isoindolo[1,2-b]quinazoline; IMDAF